THE EFFECT OF EMOTIONAL INTELLIGENCE AND ADVERSITY QUETIONT OF SCHOOL STUDENTS ON MATHEMATICAL LEARNING RESULTS STUDENTS OF SMP N 2 NANGGULAN - Pupus Winandari; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Emotional intelligence and Adversity Quotient of students in SMP N 2 Nanggulan are still relatively low due to lack of sympathy, sense of responsibility, and irritability. This is thought to result in low mathematics learning outcomes. This study aims to determine: a significant influence between emotional intelligence and adversity quotient of students in school on mathematics learning outcomes of students of class VIII odd semester of SMP N 2 Nanggulan, Kulon Progo Regency 2015/2016 academic year. The population in this study were students of class VIII SMP N 2 Nanggulan, Kulon Progo Regency in the academic year 2015/2016, consisting of classes VIII A, VIII B, VIII C, totaling 96 students. Class VIII A as a trial class, Samples taken from class VIII B as experimental class 1 and class VIII C as experimental class 2. The sampling technique uses saturated sampling techniques. Data collection techniques using non-test test methods. Data collection instruments in the form of questionnaires and multiple-choice questions. The data collection instrument test uses a validity test, a reliability test, and a different power test. The data analysis technique used is the prerequisite test analysis including normality test and homogeneity test, followed by hypothesis testing using 2x2 Factorial Design. Finally, use the t-test to compare the high and low average of each instrument. The results showed that: (1) there was an influence of emotional intelligence on mathematics learning outcomes, evidenced by = 4,859439652 ≥   =4, 0039 at a significant level of 5%, db: V1 = 1 and V2 = 59, (2) there is an effect of adversity quotient on mathematics learning outcomes, evidenced by   = 6,265821956 ≥   =4,0039 at a significant level of 5%, db: V1 = 1 and V2 = 59, (3) there is an influence of emotional intelligence and adversity quotient on mathematics learning outcomes, evidenced by = 4,528768652 ≥  = 4,0039 at a significant level of 5%, db: V1 = 1 and V2 = 59. Then from the results of Tukey's HSD test showed that the third treatment (low emotional intelligence and high adversity quotient) which is the lowest average learning outcomes.